From flexibility to constraint: The contrastive use of lexical tone in early word learning - Hay, Jessica F. (Child Dev, 2014)
Infants must develop both flexibility and constraint in their interpretation of acceptable word forms. The current experiments examined the development of infants’ lexical interpretation of non-native variations in pitch contour. Fourteen, 17-, and 19-month-olds (Experiments 1 and 2, N = 72) heard labels for two novel objects; labels contained the same syllable produced with distinct pitch contours (Mandarin lexical tones). The youngest infants learned the label-object mappings, but the older groups did not, despite being able to discriminate pitch differences in an object-free task (Experiment 3, N = 14). Results indicate that 14-month-olds remain flexible regarding what sounds make meaningful distinctions between words. By 17–19 months, experience with a non-tonal native language constrains infants’ interpretation of lexical tone.